Psychological Skills of Sports Children and Talented Sports Children: Comparative Study: A Comparative Study on the Psychological Skills of Sports Children and Talented Sports Children (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The people believes that 50-90% of performances depend on the sport participants psychological skills. Psychological skills are especially important when facing an opponent with similar physical abilities. Psychological factors can explain, why sports participants performance can vary from day to day, without changes in physical condition (Weinberg & Gould, 2011). Therefore, the achievements of psychology had become more and more important in professional sports as well as in psychological aspects. Sports children, for winning in the competition what all skills are they using. In the training session they will learn how to face opponent physically, as well they will use psychological skills too. The aim of the study is to know what are the psychological skills are using and how the psychological skills are enhancing their performance, whether these psychological skills are more in the talented sports children or non-talented. Keeping the above points in view, present study tries to explore the psychological skills of the sports children and talented sports children. 30 children are been participated from talented sports children and 30 from sports children, they were selected using convenient sampling technique. Psychological skill inventory for sports (PSIS-R-5) was developed by Mahoney et al., 1987 used to measure the psychological skills of the sports. The talented sports children obtained higher mean score in all psychological skills. The obtained results shows that talented sports children have significantly better psychological skills compare to sports children.